PARENTAL INVOLVEMENT IN MATHEMATICS LEARNING : A SYSTEMATIC LITERATURE REVIEW FROM SOCIAL, PYSCHOLOGICAL, AND ACADEMIC PERSPECTIVES (International Journal of Cultural and Social Science, 2026)
Parental involvement in mathematics learning is a key predictor of students' mathematical achievement, yet existing studies examine this relationship through single-dimensional lenses (social, psychological, or academic) producing fragmented understanding. This Systematic Literature Review (SLR) follows PRISMA 2020 guidelines, searching six databases (Scopus, Web of Science, ERIC, PsycINFO, SpringerLink, Google Scholar) for studies published 2014–2026. After four-stage screening (Cohen's k = 0.79–0.84), 32 open-access studies were included. Quality was assessed using MMAT 2018, AMSTAR-2, and CASP. Three convergent findings emerged: (1) socioeconomic status (SES) is the primary structural predictor of parental involvement quality, operating through mediating pathways of parental expectations, investment capacity, and psychological readiness; (2) parental math anxiety combined with frequent homework assistance constitutes an active mechanism of intergenerational transmission of low mathematics achievement [7, 21, 23]; (3) systematic misalignment exists between HOTS-based school curricula and parents' procedural mathematical understanding, compounded by weak teacher–parent communication. These three dimensions form a cyclical causal system with reinforcing feedback loops, mediated by students' mathematics self-efficacy and mental health [29, 26]. Effective interventions must target all three dimensions simultaneously: reducing parental math anxiety, bridging curriculum knowledge gaps through structured parent workshops, and strengthening teacher–parent communication. This study contributes an integrative causal model as a foundation for designing contextually responsive parental involvement programs in the Southeast Asian educational context.